The effectiveness of service recovery and its role in building long-term relationships with customers in a restaurant setting - Ok, Chihyung (Kansas State University, 2004)
This study proposed and tested a theoretical model of service recovery consisting of antecedents and consequences of service recovery satisfaction. This study further tested recovery paradox effects and investigated the effects of situational and attributional factors in the evaluation of service recovery efforts and consequent overall satisfaction and behavioral intentions. The study employed scenario experimentation with three dimensions of justice manipulated at two levels each (2x2x2 between-groups factorial design). Postage paid, self-addressed envelopes and questionnaires (600 copies) were distributed. Participants represented 15 religious and community service groups. All respondents were regular casual restaurant customers. Of 308 surveys returned, 286 cases were used for data analysis. In study 1, the proposed relationships were tested using the structural equation modeling. In study 2, multivariate analysis of variance and multivariate analysis of covariance tests were employed to test proposed hypotheses. The three dimensions of justice had positive effects on recovery satisfaction. Recovery satisfaction had a significant positive effect on customers’ trust. Trust in service providers had positive effect on commitment and overall satisfaction. Commitment had positive effects on overall satisfaction and behavioral intentions. This study indicated that, although a service failure might negatively affect customers’ relationship with the service provider, effective service recovery reinforced attitudinal and behavioral outcomes. The results of this study emphasized that service recovery efforts should be viewed not only as a strategy to recover customers’ immediate satisfaction but also as a relationship tool to provide customers confidence that ongoing relationships are beneficial to them. This study did not find recovery paradox in the experimental scenarios. The magnitude of service failure had significant negative effects on perceived justice and recovery satisfaction. Customers’ rating of stability causation had significant negative effects on overall satisfaction, revisit intention, and word-of-mouth intention. The study findings indicated that positive recovery efforts could reinstate customers’ satisfaction and behavioral intentions up to those of pre-failure. Restaurant managers and their employees need to provide extra efforts to restore the customers’ perceived losses in serious failure situations. Service providers should reduce systematic occurrences of service failure so customer will not develop stability perception.
Keywords: Service recovery; Recovery satisfaction; Justice theory; Trust; Commitment; Behavioral intentions; Business Administration, General (0310)